Body adiposity is associated with risk of high blood pressure in Portuguese schoolchildren - Rodrigues, Paulo Rogério Melo (2018)
The aim of the study was to estimate the prevalence of high blood pressure (HBP) and its association with anthropometric indicators of adiposity in Portuguese schoolchildren. Methods: In this cross-sectional study, a nationally representative sample of 6-9-year-old children was analyzed. Weight and height (used to calculate body mass index [BMI]), blood pressure (BP), waist circumference (WC) and skinfold thickness (used to estimate body fat percentage [BFP]) were measured using standard techniques. BP was classified as high-normal BP or hypertension for values between the 90th and 95th percentiles or above the 95th percentile, respectively. A body adiposity index was calculated with principal component analysis using BMI, WC and BFP. Multinomial logistic regression models were used to estimate the strength of the association between anthropometric indicators and HBP. Results: The prevalence of high-normal BP and hypertension was 4.5% and 3.7%, respectively. BP was positively correlated with all anthropometric indicators (p < 0.01 for all). HBP was significantly more prevalent in females than in males and was positively associated with higher values of the assessed anthropometric indicators of adiposity, especially among females. Conclusion: Increased body fat predicted HBP. The use of anthropometric indicators may thus be useful in screening for HBP among Portuguese schoolchildren.